Genomic insights into Group A Streptococcus pathogenesis - Rampersadh, Kimona (Department of Medicine, 2026)
Group A Streptococcus (GAS) is a bacterium responsible for invasive and non-invasive infections in humans. The sequela of an untreated or undertreated GAS pharyngitis include Rheumatic Fever (RF) and Rheumatic Heart Disease (RHD). Despite evidence for the effectiveness of antibiotics such as penicillin, the burden of GAS remains high in low- and middle-income countries (LMICs) compared to high-income countries (HIC), thus necessitating the development of innovative prevention tools and improve treatment strategies tailored to LMICs. However, the pathogenetic role of GAS is poorly understood. There remains limited studies conducted across Africa, compared with HICs, documenting virulence profiles associated with GAS infection, despite the fact that an increased burden of GAS is seen in LMICs. Only a few whole genome sequencing (WGS) studies in GAS have been conducted in Africa, but none have been performed in Southern Africa. To address this knowledge gap, first, I conducted evidence-based reviews on virulence factors in invasive GAS disease (study 1) and antimicrobial resistance (AMR) of GAS in LMICs (study 2). Thereafter, on a collection of invasive and non-invasive GAS isolates from Cape Town, South Africa, performed antimicrobial susceptibility testing (study 3) and employed WGS to identify the frequency of virulence factors and AMR determinants (study 4). In brief, I provide comprehensive evidence-based data linking hasA, speA, speK, and speG to invasive GAS infections, while factors like smeZ, ssa, and sic show inverse associations; document penicillin's continued high efficacy, alongside notable resistance to macrolides and tetracycline observed in LMICs; I demonstrate low levels of antimicrobial resistance in GAS in Cape Town, with most antibiotics being effective and only minimal resistance to macrolides and tetracycline; I report that GAS isolates from Cape Town exhibit a diverse range of virulence factors and AMR genes, with notable geographic variations. My research contributes to the growing evidence base to inform future efforts at global control of GAS infections. In addition to confirming antibiotic sensitivities peculiar to our setting, suggest that GAS profile variations should be taken into account to gain a deeper understanding of GAS infection in a local context.